Pendekatan Regresi Linear untuk Mengkaji Pengaruh Induktansi pada Efisiensi dan Daya Keluaran Zeta Converter - Wiryajati, I Ketut; Baihaki, Ahmad Riki; Budiman, Djul Fikry (Depertment of Electrical Engineering University of Mataram, 2024)
Increasing security on vehicles, including electric bicycles, is an important concern to prevent criminal acts such as theft. The security system developed in this study uses a fingerprint sensor to ensure that only registered users can operate electric bicycles. By scanning and verifying fingerprints, the system ensures that only fingerprints registered in the database can start the vehicle. E-bike technology, which combines the concept of a conventional bicycle with the addition of an electric motor and battery as a driver, was chosen as the object of research. The implementation of this system involves an Arduino Uno device, fingerprint sensor, buzzer, and relay to regulate vehicle access. Arduino Uno functions as a control center that regulates the process of verifying identity and activating electric bicycles, while the buzzer acts as a sound notification tool in the system. This system is expected to be able to improve vehicle security and provide a practical solution in vehicle access based on biometric authentication.